2012
DOI: 10.2174/1874205x01206010071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rotating Acoustic Stimulus on Heart Rate Variability in Healthy Adults

Abstract: Acoustic stimulus can modulate the Autonomic Nervous System. However, previous reports on this topic are conflicting and inconclusive. In this study we have shown, how rotating acoustic stimulus, a novel auditory binaural stimulus, can change the autonomic balance of the cardiac system. We have used Heart rate Variability (HRV), an indicator of autonomic modulation of heart, both in time and frequency domain to analyze the effect of stimulus on 31 healthy adults.A decrease in the heart rate accompanied with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 36 publications
3
14
0
Order By: Relevance
“…Moreover, this result is in agreement with the current literature showing the crucial role of LPP analysis during acoustic elicitation [70]- [74]. Among the other LPP measures, the SD1 measures, which represents the instantaneous beat-to-beat variability of RR intervals, and SD12, which represents the ratio between the two standard deviations, have been associated to the parasympathetic activity [43], [75], [76]. Thus, a decrease of these indices could be associated to a corresponding reduction of the parasympathetic modulation.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Moreover, this result is in agreement with the current literature showing the crucial role of LPP analysis during acoustic elicitation [70]- [74]. Among the other LPP measures, the SD1 measures, which represents the instantaneous beat-to-beat variability of RR intervals, and SD12, which represents the ratio between the two standard deviations, have been associated to the parasympathetic activity [43], [75], [76]. Thus, a decrease of these indices could be associated to a corresponding reduction of the parasympathetic modulation.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…A relevant contribution was given by nonlinear parameters of defined by LPP. This finding confirms the relevant contribution of nonlinear analysis in the affective computing field, especially in the analysis of cardiac signals [5], [43], [70]. Moreover, this result is in agreement with the current literature showing the crucial role of LPP analysis during acoustic elicitation [70]- [74].…”
Section: Conclusion and Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We wonder whether acoustic stimulation reduces the global HRV. Conversely, Roy and co-workers (19) investigated the effects of a novel auditory binaural stimulus, called rotating acoustic stimulus, on the cardiac autonomic responses. The authors observed a decrease in the HR and an increase in the time domain RMSSD, SD1, SD2 and the SD1/SD2 ratio after the stimulation.…”
Section: Discussionmentioning
confidence: 99%